Psychological Contract Breach, Stress and Employee Engagement During and After COVID-19: The Role of Inclusive Leadership - Parku, Kenneth; Obuobisa-Darko, Theresa; Amoako Asiedu, Emelia (APPS Publications, 2022)
This study extends both Social Exchange Theory and the Job Demands –Resources model by examining the connection between psychological contract breach, job stress and employee engagement in relation to the role inclusive leadership plays. Using a quantitative approach, data was gathered from two hundred and two (202) respondents, selected using convenience sampling technique. Data gathered was analysed using SPSS version 26 and SmartPLS 4. Results showed that Job Stress had a negative statistically significant impact on Inclusive Leadership Employee Engagement, Innovative Output and Turnover Intent. Inclusive Leadership Psychological Contract Breach had a positive significant relationship with Innovative Output but a negative relationship with Job Stress. The study also found out that Job Stress mediates the relationship between Inclusive Leadership Psychological Contract Breach and Inclusive Leadership Employee Engagement. The study contributes to clarifying and extend the social exchange theory (SET) by unravelling how the inclusive leader operates on respect, recognition, responsiveness and responsibility, in the reciprocal relationship between himself and their subordinates. Additionally, the study identifies the relationship between psychological contract breach, job stress and employee engagement in a developing country after the COVID-19 pandemic.